EU Budget Milestones: From Fundamental Systemic Reforms to Organised Chaos - Szemlér, TAMÁS (Papeles del Este, 2006)
In this paper, the four “milestones” of the EU budget, the four main packages related to the mid-term financial perspectives are being examined. The overall tendency seems to be clear: in 1988 the Delors I. package has created the basic features of a system that has been later adjusted several times, and for today, we arrived at a point, where it is hard to be seen because of the jungle o modifications. Time is running fast – it is now that we have to begin to think about how the new system should look like, if we are interested in making Europe dynamic, innovative and competitive on the long run.